Cdc14 phosphatase contributes to cell wall integrity and pathogenesis in Candida albicans - Milholland, Kedric L.; AbdelKhalek, Ahmed; Baker, Kortany M.; Hoda, Smriti; DeMarco, Andrew G.; Naughton, Noelle H.; Koeberlein, Angela N.; Lorenz, Gabrielle R.; Anandasothy, Kartikan; Esperilla-Muñoz, Antonio; Narayanan, Sanjeev K.; Correa-Bordes, Jaime; et al. (Frontiers in Microbiology, 2023)
The Cdc14 phosphatase family is highly conserved in fungi. In Saccharomyces cerevisiae, Cdc14 is essential for down-regulation of cyclin-dependent kinase activity at mitotic exit. However, this essential function is not broadly conserved and requires only a small fraction of normal Cdc14 activity. Here, we identified an invariant motif in the disordered C-terminal tail of fungal Cdc14 enzymes that is required for full enzyme activity. Mutation of this motif reduced Cdc14 catalytic rate and provided a tool for studying the biological significance of high Cdc14 activity. A S. cerevisiae strain expressing the reduced-activity hypomorphic mutant allele (cdc14hm) as the sole source of Cdc14 proliferated like the wild-type parent strain but exhibited an unexpected sensitivity to cell wall stresses, including chitin-binding compounds and echinocandin antifungal drugs. Sensitivity to echinocandins was also observed in Schizosaccharomyces pombe and Candida albicans strains lacking CDC14, suggesting this phenotype reflects a novel and conserved function of Cdc14 orthologs in mediating fungal cell wall integrity. In C. albicans, the orthologous cdc14hm allele was sufficient to elicit echinocandin hypersensitivity and perturb cell wall integrity signaling. It also caused striking abnormalities in septum structure and the same cell separation and hyphal differentiation defects previously observed with cdc14 gene deletions. Since hyphal differentiation is important for C. albicans pathogenesis, we assessed the effect of reduced Cdc14 activity on virulence in Galleria mellonella and mouse models of invasive candidiasis. Partial reduction in Cdc14 activity via cdc14hm mutation severely impaired C. albicans virulence in both assays. Our results reveal that high Cdc14 activity is important for C. albicans cell wall integrity and pathogenesis and suggest that Cdc14 may be worth future exploration as an antifungal drug target.